Social Transformation Through Dhikr: Thoriqoh Naqsyabandiyah's Da'wah Strategy in Central Java - Yasfin, Moh Anwar; khotimatuzzahro', khotimatuzzahro' (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2025)
This study describes the da'wah strategy applied by Thoriqoh Naqsyabandiyah Al-Khalidiyah in Central Java as a representation of Sufistic da'wah that is integrative and adaptive in responding to the challenges of modernity. This order not only focuses on the spiritual dimension through the internalization of dhikr khofi and the practice of muraqabah, but also implements a da'wah bil-hal approach, namely da'wah through concrete examples in the social sphere. Using a qualitative approach, data was collected through in-depth interviews, documentation studies, and participatory observation of the community of worshipers in the Demak area. The research findings indicate that the tarekat's da'wah strategy is built on the foundation of three main dimensions as proposed in Al-Bayanuni's theory: emotional-spiritual ('athifi), rational-intellectual ('aqli), and empirical-behavioral ('hissi) dimensions. Such strategies not only contribute to the formation of individual spiritual character, but also strengthen social solidarity and form an inclusive religious society. Another specialty of this Thoriqoh is its ability to contextualize Sufistic values with local culture, such as through the use of tembang macapat in dhikr activities and recitation assemblies. Thus, Thoriqoh Naqsyabandiyah Al-Khalidiyah functions not only as a means of spiritual development, but also as a catalyst for social change that is transformative, contextual, and far-reaching in the midst of the diversity of Central Java society. Kajian ini menguraikan strategi dakwah yang diterapkan oleh Thoriqoh Naqsyabandiyah Al-Khalidiyah di Jawa Tengah sebagai representasi dakwah sufistik yang bersifat integratif dan adaptif dalam merespons tantangan modernitas. Tarekat ini tidak hanya menitikberatkan pada dimensi spiritual melalui internalisasi dzikir khofi dan praktik muraqabah, tetapi juga mengimplementasikan pendekatan dakwah bil-hal, yakni dakwah melalui keteladanan konkret dalam ranah sosial. Dengan pendekatan kualitatif, data dikumpulkan melalui wawancara mendalam, studi dokumentasi, serta observasi partisipatif terhadap komunitas jamaah di wilayah Demak. Temuan penelitian mengindikasikan bahwa strategi dakwah tarekat ini dibangun di atas fondasi tiga dimensi utama sebagaimana dikemukakan dalam teori Al-Bayanuni: dimensi emosional-spiritual (‘athifi), rasional-intelektual (‘aqli), dan dimensi empiris-perilaku (‘hissi). Strategi tersebut tidak hanya berkontribusi pada pembentukan karakter spiritual individu, tetapi juga memperkuat solidaritas sosial dan membentuk masyarakat religius yang inklusif. Keistimewaan lain dari Thoriqoh ini adalah kemampuannya dalam mengontekstualisasikan nilai-nilai sufistik dengan budaya lokal, seperti melalui pemanfaatan tembang macapat dalam aktivitas dzikir dan majelis pengajian. Dengan demikian, Thoriqoh Naqsyabandiyah Al-Khalidiyah berfungsi tidak hanya sebagai sarana pembinaan spiritual, melainkan juga sebagai katalisator perubahan sosial yang transformatif, kontekstual, dan berdaya jangkau luas di tengah keberagaman masyarakat Jawa Tengah.